Inappropriate Use of Submission and Rejection Emails for Advertising Revision Services and Congresses - Teixeira da Silva, Jaime A. (ETHICS IN PROGRESS, 2023)
Finding a niche journal for the submission of an academic paper can sometimes be a challenge for authors, and finding the right choice may involve a series of submissions and rejections. Emails from editors and journals related to the submission or rejection of a paper should be strictly related to these purposes, i.e., to inform authors that their paper has been received, outline the subsequent editorial handling or peer reviewer steps in the former, or the reasons for rejection in the latter. This paper highlights four cases of - in the author’s opinion - the abuse of such emails by COPE member journals and publishers (Emerald Publishing Ltd., Springer Nature, Elsevier, Wiley) to advertise for-profit English revision and editing services and/or conferences, as a way to maximize these emails for a dual purpose, namely to inform authors of submission-related aspects (valid communication) while also trying to obtain clients and thus business for non-submission-related aspects (invalid communication). Since an abuse of email-based communication for non-academic purposes is an ethics-related matter, there is a need for systematic research of this potential abuse of emails from both COPE member and non-member journals.